2011
DOI: 10.1037/a0022832
|View full text |Cite
|
Sign up to set email alerts
|

“What about me?” Perceptions of exclusion and Whites' reactions to multiculturalism.

Abstract: A 5-study investigation of reactions of dominant group members (i.e., White Americans) to diversity (relative to racial minority reactions) provides evidence of implicit and explicit associations between multiculturalism and exclusion and of a relationship between perceived exclusion and reactions to diversity. In Study 1, Whites but not racial minorities were faster in an implicit association task at pairing multiculturalism with exclusion than with inclusion. This association diminished in Study 2 through a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
399
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(421 citation statements)
references
References 108 publications
(149 reference statements)
14
399
3
5
Order By: Relevance
“…Kesler and Bloemraad's (2010) 19-country study showed that multicultural policies increase a sense of belonging, defined in terms of civic participation. However, despite these positive outcomes, multicultural policies have often been misunderstood as exclusionary and perceived as threatening by members of the dominant ethno-cultural group (Plaut, Garnett, Buffardi, & Sanchez-Burks, 2011). Current debates in the United States focus on the merits of multicultural versus color-blind ideologies and policies.…”
Section: Multiculturalism Policies Internationallymentioning
confidence: 99%
See 1 more Smart Citation
“…Kesler and Bloemraad's (2010) 19-country study showed that multicultural policies increase a sense of belonging, defined in terms of civic participation. However, despite these positive outcomes, multicultural policies have often been misunderstood as exclusionary and perceived as threatening by members of the dominant ethno-cultural group (Plaut, Garnett, Buffardi, & Sanchez-Burks, 2011). Current debates in the United States focus on the merits of multicultural versus color-blind ideologies and policies.…”
Section: Multiculturalism Policies Internationallymentioning
confidence: 99%
“…This strategy is associated with a stronger racial bias, bringing with it negative consequences in educational and organizational settings (Apfelbaum, Norton, & Sommers, 2012). In contrast, multicultural models of diversity are associated with greater inclusiveness, reduced racial bias, and more engagement from non-dominant groups (Plaut et al, 2011;Plaut, Thomas, & Goren, 2009). Overall, multicultural approaches have been shown to promote "positive psychological, educational and organizational outcomes for minorities and organizations" (Plaut et al, 2011, p. 2).…”
Section: Multiculturalism Policies Internationallymentioning
confidence: 99%
“…An exception is a series of US-based studies by Plaut, Garnett, Buffardi, and Sanchez-Burks (2011). They found that while cultural diversity policies that emphasize the value of diversity may be perceived positively by ethnic minority employees, such policies may actually receive low acceptance from ethnic majority employees.…”
Section: Psychological Predictors Of Workplace Cultural Diversity Supmentioning
confidence: 99%
“…Other research has explored the role of multiculturalism to reduce negative experiences of diversity (see Rattan & Ambady, 2013, for a review). Interestingly, some work indicates that the '"inclusive" ideology of multiculturalism is not perceived as such by Anglos, suggesting that the purportedly inclusive message may not be able to address Anglos' potential belonging frustration (Plaut, Garnett, Buffardi, & Sanchez-Burks, 2011).…”
Section: Future Directionsmentioning
confidence: 99%